A Stated Preference Investigation into the Chinese Demand for Farmed vs. Wild Bear Bile - Dutton, Adam J.; Hepburn, Cameron; Macdonald, David W. (PLOS ONE, 2011)
Farming of animals and plants has recently been considered not merely as a more efficient and plentiful supply of their products but also as a means of protecting wild populations from that trade. Amongst these nascent farming products might be listed bear bile. Bear bile has been exploited by traditional Chinese medicinalists for millennia. Since the 1980s consumers have had the options of: illegal wild gall bladders, bile extracted from caged live bears or the acid synthesised chemically. Despite these alternatives bears continue to be harvested from the wild. In this paper we use stated preference techniques using a random sample of the Chinese population to estimate demand functions for wild bear bile with and without competition from farmed bear bile. We find a willingness to pay considerably more for wild bear bile than farmed. Wild bear bile has low own price elasticity and cross price elasticity with farmed bear bile. The ability of farmed bear bile to reduce demand for wild bear bile is at best limited and, at prevailing prices, may be close to zero or have the opposite effect. The demand functions estimated suggest that the own price elasticity of wild bear bile is lower when competing with farmed bear bile than when it is the only option available. This means that the incumbent product may actually sell more items at a higher price when competing than when alone in the market. This finding may be of broader interest to behavioural economists as we argue that one explanation may be that as product choice increases price has less impact on decision making. For the wildlife farming debate this indicates that at some prices the introduction of farmed competition might increase the demand for the wild product.